Pancasila sebagai Landasan Komunikasi yang Berkeadilan an Berkelanjutan - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Zaki Ramdhani Wicaksono; Muhammad Asziv Amalia; Ruditri Setyawan; Aprilia Ningpitasari (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Pancasila is foundational ideology of Indonesia, serving as a guiding principle across various aspects of life, including fair and sustainable communication. Klean (2013) states that "Pancasila is a source of values for building just and civilized social interaction." In the context of communication, the principle of justice is crucial, as "every individual has the equal right to express their opinion." This study utilizes a qualitative method Based on an analysis of existing research and discourse analysis. This method was chosen to understand the application of Pancasila values in the context of fair and sustainable communication in the social, political, and mass media spheres. The study is descriptive-analytical in nature, aiming to explain, analyze, and interpret the concept of communication based on Pancasila in various life aspects. Pancasila functions not only as the foundation of the state but also as a philosophical system that holds significant meaning and relevance for the Indonesian nation in preserving unity and national integrity. As a foundation for fair and sustainable communication, Pancasila plays a vital role in multiple life domains by offering five interrelated and complementary principles.